Seeing Gravity: Gait Adaptations to Visual and Physical Inclines – A Virtual Reality Study - Cano Porras, Desiderio; Zeilig, Gabriel; Doniger, Glen M.; Bahat, Yotam; Inzelberg, Rivka; Plotnik, Meir (Frontiers in Neuroscience, 2020)
Using advanced virtual reality technology, we demonstrate that exposure to virtual inclinations visually simulating inclined walking induces gait modulations in a manner consistent with expected gravitational forces (i.e., acting upon a free body), suggesting vision-based perception of gravity. The force of gravity critically impacts the regulation of our movements. However, how humans perceive and incorporate gravity into locomotion is not well understood. In this study, we introduce a novel paradigm for exposing humans to incongruent sensory information under conditions constrained by distinct gravitational effects, facilitating analysis of the consistency of human locomotion with expected gravitational forces. Young healthy adults walked under conditions of actual physical inclinations as well as virtual inclinations. We identify and describe ‘braking’ and ‘exertion’ effects – locomotor adaptations accommodating gravito-inertial forces associated with physical inclines. We show that purely visual cues (from virtual inclinations) activate a mechanism of indirect prediction, inducing consistent locomotor adaptations to counter expected gravity-based changes. Specifically, downhill visual cues activate the braking effect in anticipation of a gravitational boost, whereas uphill visual cues promote an exertion effect in anticipation of gravitational deceleration. Although participants initially rely upon vision to accommodate environmental changes, a sensory reweighting mechanism gradually reprioritizes body-based cues over visual ones. A high-level neural model outlines a putative pathway subserving the observed effects. Our findings may be pivotal in designing virtual reality-based paradigms for understanding perception and action in complex environments with potential translational benefits.